Success Factors for Creating Spin-Out Companies by South African Publicly Financed Research and Development Institutions: A Resource-Based View Perspective - P Langa; E.I Edoun; V. Naidoo (Journal of Economics and Behavioral Studies, 2018)
Technology commercialisation using spin-out companies has shown to be a viable option by publicly financed research and development (R&D) institutions internationally. In South Africa (SA) this trend of spin-out company creation for technology commercialisation is anticipated to be on the rise since the inception of the Intellectual Property Rights from Publicly Financed Research and Development Act number 51 of 2008 (IPR-PFRD Act). This study aimed at trying to understand the factors that influence the successful creation of spin-out companies by SA publicly financed R&D institutions, utilising the RBV as the main theoretical framework. A survey questionnaire was distributed using a purposive sample approach to 49 key individuals (technology transfer professionals) who have been involved in spin-out creation in the past and the response was received from 17 respondents. A mixed methods research methodology was utilised and the data was presented using descriptive statistics and narration. The results of the data indicate a similar pattern to international trends and in some instances unique resource combinations that are relevant to SA.